The Model of School and Community Relationship Management Based on Malay Culture at SD Negeri 105 Pekanbaru - Lestari, Anggun Riski; Isjoni, Isjoni; Erlisnawati, Erlisnawati (LPPM Institut Pendidikan Nusantara Global, 2025)
In response to global educational dynamics, there is a growing need for innovative collaboration between schools and communities that is deeply rooted in local cultural values. This study aims to develop the Model of School and Community Relationship Management Based on Malay Culture (MHSM-BM Model) and to evaluate its effectiveness, along with the challenges encountered during its implementation at SD Negeri 105 Pekanbaru. Utilizing a Research and Development approach guided by the ADDIE model, data were collected through observation, interviews, and document analysis, and were analyzed using techniques of data reduction, presentation, and conclusion drawing. The development of the MHSM-BM model proceeded through five stages: analyzes, which examined existing relationships between schools and stakeholders; design, which integrated Epstein’s framework with twelve principles of Tunjuk Ajar Melayu that reflect the social values of the Malay community; development, involving validation by two expert assessors; implementation, where the model was applied in the school context; and evaluation, which assessed its overall effectiveness. The findings indicate that the model achieved a high level of effectiveness, with student and parental engagement exceeding 90 percent, supported by six key frameworks: pembinaan budi pekerti (character development), dialog dua arah (two-way dialogue), kepedulian sosial (social care), pembelajaran berkelanjutan (sustainable learning), pengambilan keputusan bijaksana (wise decision-making), and kolaborasi berdaya (empowered collaboration). However, challenges remain, particularly in maintaining ongoing collaboration among educators, students, and parents. Overall, the MHSM-BM model presents significant potential for broader application as a means to establish harmonious collaboration between schools and stakeholders.